Insurance of management system of the investment project risk. (Journal of Economic Research & Business Administration, 2015)
Insurance is one of the important areas of financial risk management in the activity of economic entities. Insurance instruments provide protection against possible adverse financial consequences of risk. Most often, the identification of possible insurance provides benefits in the future in the preparation of investment projects. Insurance risks of investment projects have features that should be considered when investing financial resources to generate income in the future. The article describes the foreign practice of insurance on insurance indicators in investment projects, application security, ways to minimize investment risks, factors of insurance activities for business, calculated values ​​of the insurance financial reserve investor. Methods for further management of insurance risks to improve implementation of investment projects are offered in this article
Keywords: Insurance; management; risks; investment project; the insurance reserve